2007
DOI: 10.1001/archpsyc.64.12.1409
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Genetic and Environmental Influences on Disordered Eating Across Adolescence

Abstract: Findings highlight the transition from early to mid adolescence as a critical time for the emergence of a genetic diathesis for disordered eating. The increase in genetic effects during this developmental stage corroborates previous research implicating puberty in the genetic etiology of eating disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
142
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(161 citation statements)
references
References 38 publications
17
142
1
1
Order By: Relevance
“…Little-to-no genetic effects (~0-5%) on disordered eating have been observed in preadolescent female twins, as shared and nonshared environmental factors have predominated (Klump et al 2000(Klump et al , 2007a. In contrast, similar and substantial genetic effects (>50%) were observed from mid-to late adolescence, with the remaining variance accounted for by nonshared environmental influences (Klump et al 2000(Klump et al , 2007a. Developmental changes in genetic and environmental effects on disordered eating symptoms have also been reported in other samples of twins.…”
Section: Puberty and The Heritability Of Disordered Eating Symptomsmentioning
confidence: 81%
See 1 more Smart Citation
“…Little-to-no genetic effects (~0-5%) on disordered eating have been observed in preadolescent female twins, as shared and nonshared environmental factors have predominated (Klump et al 2000(Klump et al , 2007a. In contrast, similar and substantial genetic effects (>50%) were observed from mid-to late adolescence, with the remaining variance accounted for by nonshared environmental influences (Klump et al 2000(Klump et al , 2007a. Developmental changes in genetic and environmental effects on disordered eating symptoms have also been reported in other samples of twins.…”
Section: Puberty and The Heritability Of Disordered Eating Symptomsmentioning
confidence: 81%
“…Cross-sectional (Klump et al 2000) and longitudinal (Klump et al 2007a;Silberg and Bulik 2005) twin studies have indicated age-related differences in genetic and environmental effects on disordered eating symptoms in females during adolescence. Little-to-no genetic effects (~0-5%) on disordered eating have been observed in preadolescent female twins, as shared and nonshared environmental factors have predominated (Klump et al 2000(Klump et al , 2007a. In contrast, similar and substantial genetic effects (>50%) were observed from mid-to late adolescence, with the remaining variance accounted for by nonshared environmental influences (Klump et al 2000(Klump et al , 2007a.…”
Section: Puberty and The Heritability Of Disordered Eating Symptomsmentioning
confidence: 99%
“…Thus, discrepant findings may be due to age differences in genetic and environmental effects. Other studies have found developmental differences in genetic effects across adolescence 9,28 but no studies have examined developmental differences from early-to middle-adulthood. The peak period of risk for disordered eating increases through young adulthood and then plateaus.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect evidence suggests that ovarian hormones may contribute to the genetic diathesis of binge eating, as genetic risk for disordered eating becomes prominent during estrogen activation at puberty (Klump et al 2003(Klump et al , 2007a. Ovarian hormones are potent regulators of gene transcription (Ostlund et al 2003) in neurotransmitter systems that are implicated in the etiology of disordered eating (e.g.…”
Section: Discussionmentioning
confidence: 99%